A Comprehensive Study on the Relationship between User Experience of Mobile Learning Platforms and Academic Anxiety among College Students - Lu, Lei (International Journal of Interactive Mobile Technologies (iJIM), 2025)
With the rapid advancement of information technology, mobile learning platforms have become essential tools for college students to acquire knowledge and enhance their academic performance. However, the widespread use of these platforms has also introduced potential issues such as academic anxiety, adversely affecting students’ learning outcomes and mental health. Existing research indicates a close correlation between the user experience of mobile learning platforms and students’ academic performance and psychological states. A thorough exploration of this relationship can aid in optimizing platform design, enhancing student learning efficiency, and alleviating academic anxiety. Current research methods primarily employ descriptive statistics and correlation analysis, lacking systematic quantitative analysis and the application of modern data mining techniques. This paper utilizes advanced clustering analysis methods to systematically investigate the relationship between college students’ user experiences on mobile learning platforms and their academic anxiety. The study includes predictive modeling based on clustering analysis and a detailed examination and validation of experimental results. The aim of this study is to unveil the intrinsic link between mobile learning platform user experience and academic anxiety, providing a scientific basis for improving platform design and optimizing user experience, thereby promoting the holistic development of college students and enhancing educational quality.